Cyclic stability of two-way shape memory effect in aged Ni50.3Ti32.2Hf17.5 polycrystals after various thermomechanical treatments - Panchenko, Elena Yu; Tagiltsev, Anton I.; Timofeeva, Ekaterina E.; Chumlyakov, Yuri I.; Marchenko, Ekaterina S. (Materials)
In the present paper, the cyclic stability of the high-temperature two-way shape memory effect was studied in high-strength Ni50.3Ti32.2Hf17.5 polycrystals after various thermomechanical treatments—training (thermocycling under stress) and stress-induced martensite aging. The effect of training and stress-induced martensite aging on the microstructure, the two-way shape memory effect, and its cyclic stability was determined. It was found out that both thermomechanical treatments induce the high-temperature two-way shape memory effect at T > 373 K, with a strain of 1.5% in tension. The influence of cyclic tests (up to 100 stress-free cycles of cooling/heating) on the two-way shape memory effect strain, the transformation temperatures, and the microstructure was established. Different degradation mechanisms of the two-way shape memory effect were established after thermocycling and stress-induced martensite aging.